Freezing Seeds and Making Futures: Endangerment, Hope, Security, and Time in Agrobiodiversity Conservation Practices. (10th December 2017) - Harrison, Rodney
Abstract: This paper considers the temporal practices inherent in the work of global agrobiodiversity conservation, drawing on ongoing research with the Nordic Genetic Resource Centre and the Svalbard Global Seed Vault. It contrasts the distinctive, future‐making practices inherent in the work of ex situ cold seed storage, with the normative, entropic view of the relationship of species diversity with time that arises from the field of biodiversity conservation more generally. These differences point to the value of comparative studies of natural and cultural heritage conservation practices that focus on their politics and ontologies to reveal the heterogeneity of approaches across these fields, and the different worlds they each produce in conserving their endangered objects for the future.